282 EPIDEMIOLOGICAL TREND OF AMYLOIDOSIS AND AMYLOIDOSIS WITH CARDIOVASCULAR COMPLICATIONS IN VENETO REGION FROM 2010-2020. (15th December 2022) - Licchelli, Luca; De Michieli, Laura; Sinigiani, Giulio; Cideni, Francesco; Troiani, Monica; Iliceto, Sabino; Cipriani, Alberto
Abstract: Background: Cardiac amyloidosis (CA) is classified as a rare disorder; however, emerging evidence exists that it might be more frequent than expected, especially in certain selected population like patients with carpal tunnel syndrome (CTS). A few studies reported a progressively increasing frequency of CA diagnosis over time, related to the availability of non-invasive diagnostic algorithm and of novel therapies. The aim of this study was to analyse CA diagnosis trend in the Veneto region over the last ten years and the possible relation with CTS diagnosis. Methods: Retrospective observational study based on discharge diagnoses ICD codes of patients hospitalized in the Veneto region between 2010 and 2020. We included patients >18 years old with ICD-9 hospital discharge codes for amyloidosis and heart failure/cardiomyopathy. Moreover, to verify the possible interaction between CTS and amyloidosis, we analysed patients with hospital or outpatient ICD-9 code for CTS surgery in the same time range. Study endpoint was to investigate if an increasing trend in CA diagnosis, overall and in high-risk patients, is present in the Veneto region. Results: Considering just the last hospitalization available for each patient, we found that the number of patients with an amyloidosis diagnosis code increased progressively from 63 individuals in 2010 to 228 individuals in 2020. This trend was more evident in males and in patients >65 years. Similarly, the numbers of hospital discharge form with a main diagnosis of amyloidosis increased from 148 in 2010 to 308 in 2020 and, again, the trend was steeper for males and for those >65 years. When we analysed those with an amyloidosis code plus a heart failure/cardiomyopathy code, we found that the number of patients increased progressively from 15 in 2010 to 159 in 2020, with a cumulative total of 556 patients. In particular, the number of males with these characteristics increased from 6 to 107, while the number of females increased from 9 to 52 patients; among those >65 years, the number of patients increased from 13 to 127 whilst it changes from 2 to 32 in those ≤65 years. When considering CTS hospital and outpatient surgery codes, we found a stable number of procedure/years over time, slightly decreasing in 2020. Despite a greater frequency of CTS surgery in females over the study period [50012 (69%) females with single CTS surgery versus 22357 (31%) males; 11406 (64%) females with multiple CTS surgeries versus 6526 (36%) males], when we analysed patients with multiple CTS surgeries and a heart failure/cardiomyopathy code, we found a total of 913 patients, 463 (51%) of which were males. Conclusion: In the Veneto region, over the past 10 years, we found a progressively increasing number of patients discharged with an amyloidosis diagnosis code and with amyloidosis and heart failure/cardiomyopathy diagnosis code, particularly men and individuals >65 years old. Regarding CTS surgery, despite an expected higher frequency in females, we found a greater proportion of males undergoing multiple CTS surgery and with a heart failure/cardiomyopathy code, potentially indicating CA diagnosis and, therefore, an opportunity for screening and earlier diagnosis in this setting.